IMPORTANCE OF INFORMATION TECHNOLOGY IN EDUCATIONAL DEVELOPMENT - Ziyoda Nazarova Faxriddinovna (PEDAGOGS, 2024)
This article discusses about important role of technology in educational settings. It explores the benefits of it and it’s effective sides for teaching. The author presents arguments supporting the inclusion of online tools in curricula and highlights the impact of it for overall academic success. Additionally, the article acknowledges potential challenges and offers suggestions for overcoming them. Overall, it advocates for the significance of meaning-focused language instruction that refers to an approach in language teaching and learning that prioritizes the communication of meaning over the explicit focus on isolated language forms such as grammar and vocabulary and form-focused language instruction that refers to an approach in language teaching and learning that emphasizes the explicit focus on linguistic forms such as grammar, vocabulary, pronunciation, and syntax. Furthermore, this there are more benefits of technology both adult students and junior ones and their learning process and emphasizes its role in fostering language development and enhancing learning outcomes.